Large functioning Childhood adrenocortical carcinoma (Case report) - Jabbar, Jinan A.; Fahad, Qusai A. (Journal of the Faculty of Medicine Baghdad, 2014)
We describe a large functioning non metastasizing ACC in 8 years old boy who presented with a history of precocious puberty noticed by his parents since 3 months .Ultrasound of the abdomen showed a large well defined right suprarenal mass with calcification and necrosis . MRI  showed  the mass to be hypojntense to liver on T1 and   hyperintense  to liver on T2, and  dynamic CT scan revealed a large hetrogenous  enhancing right suprarenal mass with calcification and necrosis , clear chest .Histopathology done after surgical removal reveal adrenocortical carcinoma,so we recommend to do an abdominal ultrasound to any child with precocious puberty because it is easy,cheap and non invasive , if any suprarenal mass found it should be further characterized by MRI and  dynamic conontrast enhanced CT to determine its respectability